2001
DOI: 10.1093/joc/51.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Do talk shows cultivate adolescents' views of the world? A prolonged-exposure experiment

Abstract: The traditional cultivation approach assumes (a) a uniform message across all television genres, (b) a nonselective viewing pattern in the audience, and (c) longterm effects. This study of possible effects of daily talk shows on adolescents involved a prolonged‐exposure experiment designed to evaluate effects of exposure to sequences dealing with lesbian or gay male relationships between the content of a specific genre and cultivation measures, independent of third variables. The results show that cultivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 12 publications
(23 reference statements)
1
20
0
1
Order By: Relevance
“…Given the popularity of television talk shows and criticism of their content, researchers have sought to understand possible negative effects associated with exposure to these shows (e.g., Davis & Mares, 1998;Rossler & Brosius, 2001). Uses and gratifications research has shown that a host of viewer characteristics influence these potential effects (A. M. Rubin, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Given the popularity of television talk shows and criticism of their content, researchers have sought to understand possible negative effects associated with exposure to these shows (e.g., Davis & Mares, 1998;Rossler & Brosius, 2001). Uses and gratifications research has shown that a host of viewer characteristics influence these potential effects (A. M. Rubin, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Less complex from an organizational point of view, although often less coherent, is a number of separate studies covering the same subject area but using different methods. This has been done, for example, in the case of cultivation effects of talk shows by Davis and Mares (1998), in a cross-sectional survey, and by Rössler and Brosius (2001a) in a sequential experiment. Here, the interaction of analyses of content, surveys, in-depth interviews and even various forms of experiment provides a well-rounded picture of the possible cultivation effects of television.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that television viewing is a stronger predictor of perceived reality than vice versa. Even this does not allow a definitive causal interpretation (see Rössler and Brosius, 2001a). Although the relationships here are amenable to more precise determination and interpretation, it is nevertheless the case that attitudes, estimates and reception data are collected at the same time, so that extraneous intervening variables, whose influence cannot be properly assessed, could underlie the asymmetry.…”
Section: Asymmetric Relationshipsmentioning
confidence: 93%
See 2 more Smart Citations